On the method of perturbations in the problem of elastoplastic instability of a rotating disk - Lila, D.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
In the study of the loss of stability by a rapidly rotating thin circular disk, a possible form of perturbation of the initial contour circle is elucidated. The first four approximations are obtained for the small parameter of the linearized boundary conditions and the conjugation conditions for the solutions.